Evaluation study of the content of the computer book for the fifth grade preparatory In light of learning patterns (Journal of the College of Basic Education, 2019)
This study aims at (evaluate the content of the computer book for the fifth grade preparatory in the light of learning patterns) for the academic year (2020-2019)، and to achieve this goal was adopted the descriptive analytical method، where the researcher adopted a list of four learning patterns (imaginary، analytical، logical and dynamic) according to the model Format (4mat) which includes the standard for each type of learning patterns with indicators indicating each standard where it consisted of (42) indicators in which the content of the computer book for the fifth grade preparatory with activities and evaluation questions at the end of each chapter was analyze، the validity and reliability of the analyze were confirmed when the researcher used the appropriate statistical methods to achieve the research objective، the results showed that the four learning patterns came with 876 repetitions in the content of the computer book distributed randomly and unevenly، the imaginary pattern came first with a (586) repetitions and a percentage (69%). However، when the imaginary pattern result compared to the spoken ratio for the agreement of arbitrators and specialists، it came with an average evaluation level by including it in the content of the computer book for the fifth preparatory grade. The analytical pattern came in second place with 190 repetitions and a percentage (22%) with a weak evaluation level. The logical pattern reached to (83) repetitions with a percentage (9%) and when compared to the spoken ratio، the level of inclusion in the content of the computer book with a weak evaluation level and third place، the dynamic pattern obtained (17) repetitions with a percentage (2%) and a weak evaluation level. In light of these results، the researcher recommended the following: The content of the fifth grade intermediate computer book needs to be reviewed in providing information and formulating its activities and evaluation questions.Taking into account the balance in the inclusion of learning patterns in the content of the computer book for the fifth grade preparatory so that the pattern does not overshadow the rest of the other patterns.Attention to the patterns that came at a weak evaluation level which are three patterns (analytical، logical and dynamic) out of four.Attention to the indicators of the neglected standards and indicators that received little attention in the inclusion of the content of the computer book for fifth grade preparatory.Utilize the list of standards for the format model (4mat) in the current study to conduct other studies for different educational stages.Conducting courses for teachers of computer book to help them in detecting the learning patterns of students and the use of appropriate teaching aids for those patterns.